THE PREPARATION OF LANTHANUM NICKELATES BY THE COMPONENT COPRECIPITATION METHOD: UDC 546.05'654'74 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Optimal conditions were determined for preparation of lanthanum nickelates that relate to Ruddlesden-Popper phases Lan-1La2NinO3n+1 with n=1 (La2NiO4,17) and n=2 (La3Ni2O7,02) by a coprecipitation method with the following calcination of the obtained blend. La2NiO4,17 has tetragonal syngony (space group I4/mmm; a=0,3843(2)нм, с=1,263(3)нм). La3Ni2O7,02 has orthorombic syngony (space group Fmmm) with cell parameters a=0,5445(3)нм, b=0,5389(2)нм, с=2,526(4)нм. The oxygen stoichiometry in the compounds was studied by iodometric titration techniques.
Keywords: coprecipitation, Ruddlesden–Popper phases (RPP), lanthanum nickelates, oxygen nonstoichiometry.